Exploring turnover intentions in Indonesian generation z: Emotional exhaustion, employee engagement, and job satisfaction - Adelia, Alfina; Daud, Ilzar; Azazi, Anwar; Iman Kalis, Maria Christiana; Hendri, Muhammad Irfani (Junal Ilmu Manajemen, 2024)
This study investigates individuals from Generation Z working in the banking sector in Indonesia, observing the factors influencing Turnover Intention. The study incorporates Emotional Exhaustion, Employee Engagement, Turnover Intention, and Job Satisfaction as mediating variables. The main objective is identifying the determinants of turnover intention among Generation Z employees in Indonesia. 257 participants were involved in this study through purposive sampling techniques, including Generation Z workers from the banking sector—the data obtained from the surveyed participants utilizing the AMOS 24 software. This research proves that Emotional Exhaustion significantly negatively influences job satisfaction. On the other hand, Employee Engagement significantly positively affects job satisfaction. Additionally, the level of employee engagement, job satisfaction, and status of emotional exhaustion positively impact employees' desire to switch jobs.